2006
DOI: 10.1373/clinchem.2005.058727
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Related Protein–Peptide Interactions Monitored in Real Time on Novel Peptide Chips by Surface Plasmon Resonance Imaging

Abstract: Because of its characteristics (easy preparation of the peptide chip; high-throughput, label-free, real-time detection; high specificity; and low background), this technology is suitable for screening biological samples and for large-scale studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 33 publications
0
53
0
2
Order By: Relevance
“…Proteins (10 M) or peptides (100 M) were grafted in triplicate on the gold surface of the biochip by electrochemical copolymerization, as described in Grosjean et al (20) and Cherif et al (22), respectively. The binding of specific Ab to probes (proteins or peptides) was monitored using surface plasmon res- onance imaging (SPRi).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins (10 M) or peptides (100 M) were grafted in triplicate on the gold surface of the biochip by electrochemical copolymerization, as described in Grosjean et al (20) and Cherif et al (22), respectively. The binding of specific Ab to probes (proteins or peptides) was monitored using surface plasmon res- onance imaging (SPRi).…”
Section: Methodsmentioning
confidence: 99%
“…The polymerisation step was performed by a short 100 ms electrical pulse (2 V) between the counter electrode located in the needle of the microarrayer and the prism gold layer (Cherif et al, 2006, Villiers et al, 2009). Another grafting method based on electro-deposition of diazonium-peptide adducts (Corgier et al, 2009) was also used, as indicated in the text.…”
Section: Peptide Immobilization On Goldmentioning
confidence: 99%
“…Peptide microarrays are a good alternative, as peptides are shorter and their stability less dependant on their tridimensional structure. Thus they are often used for antibody profiling (Cherif et al, 2006, Halperin et al, 2011, Neuman de Vegvar et al, 2003. However, there is no study dealing with the stability of such microarrays during a large samples screening (>20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies using peptide arrays and chips have been constructed for the high-throughput analysis [17]. Surface plasmon resonance imaging has been a powerful measurement of the interactions in real time on peptide chips [18]. Moreover, a standardized discriminative model for the prediction of proteinpeptide interactions has been constructed using computer simulation [19].…”
Section: Introductionmentioning
confidence: 99%